Cosmopolitanism over Ethnonationalism through Social Movement: The Case of Anti-CAA Movement in India - Terbi Loyi (Cosmopolitan Civil Societies: An Interdisciplinary Journal)
Ethnonationalism based on religion has had a significant impact in the modern history of India. While celebrating its diversity as a democratic nation, the country has also witnessed numerous ethnic movements, tensions, violence as well as assertion of cultural and ideological values by one dominant group over another. The ‘State’ often gets involved in these conflicts directly or indirectly. The case of Citizenship Amendment Act (CAA) of 2019 is a recent example relating to issues of citizenship and discrimination based on religion that sparked a nationwide movement. The citizens condemned the enactment of CAA as anti-democratic and against the secularistic ideology of India. Drawing upon the case of Anti-CAA movement across India the paper argues that social movements serve as a platform to revisit and realize the ideologies of cosmopolitanism.